2018
DOI: 10.2174/1874325001812010173
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Postoperative Portable Radiograph After Total Knee Replacements: A Necessity or a Burden?

Abstract: Background:Total Knee Replacement (TKR) is one of the most commonly performed orthopaedic surgery(1). Immediate postoperative portable radiographs are performed after primary TKR in order to identify any potential complications and technical flaws. It also serves as a reference for comparison with subsequent radiographs. The aim of this study was to evaluate the clinical and economical value of these radiographs in TKR. It compares the quality of the portable radiograph, taken immediately post-operation, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Several previous studies have argued that postoperative radiographs following TKA are unnecessary [6][7][8][15][16][17][18] . Moskal et al reviewed 646 TKAs over a 6-year period, of which, immediate postoperative radiographs were taken for only 12 TKAs and for the remaining 634 radiographs were delayed until follow-up 15 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several previous studies have argued that postoperative radiographs following TKA are unnecessary [6][7][8][15][16][17][18] . Moskal et al reviewed 646 TKAs over a 6-year period, of which, immediate postoperative radiographs were taken for only 12 TKAs and for the remaining 634 radiographs were delayed until follow-up 15 .…”
Section: Discussionmentioning
confidence: 99%
“…This can lead to multiple imaging attempts to obtain the proper views, leading to increased radiation exposure and time in the operating room. In a study by Aljawder et al, they compared the quality of postoperative portable recovery room Xrays with radiology suite X-rays in patients who underwent TKA 6 . After reviewing X-rays of 382 patients, they concluded that 40% of the recovery room radiographs were inadequate for analysis compared to those obtained in the radiology suite, which were all deemed to be adequate 6 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…There is sufficient evidence in the literature to suggest that routine postoperative radiographs in orthopaedic patients seldom affect the clinical outcome or management of the patients [ 13 - 15 ]. Although most of these studies have evaluated patients who underwent surgeries like total knee arthroplasty, total hip arthroplasty or spinal surgeries, we found similar results in patients being managed with hip hemiarthroplasty.…”
Section: Discussionmentioning
confidence: 99%